HIGHER EDUCATION ENROLLMENT GROWTH AS A FACTOR OF UNEMPLOYMENT (Scientific electronic journal "Labor Economics and Human Capital", 2025)
The article provides an analytical assessment of the compliance of the higher education system of Uzbekistan with the requirements of the national labor market. It is shown that the accelerated massification of higher education, with insufficient consideration of the qualitative parameters of training and structural limitations of employment, creates the risks of rising unemployment and underutilization of human capital. The analysis revealed an imbalance between the number of graduates, in-demand competencies and the actual structure of jobs. Based on the analysis, the directions of optimization of admission policy, educational standards and mechanisms of communication between universities and the labor market are proposed.
Keywords: human capital, education, investment in education, personnel training, economic growth, unemployment, employment.